Homogeneity of 16S-23S Ribosomal Intergenic Spacer Regions of Tropheryma whippelii in Swiss Patients with Whipple’s Disease - Hinrikson, Hans Peter (American Society for Microbiology, 1999)
The current genetic strategies used to identify Tropheryma whippelii, the putative agent of Whipple’s disease, are based on PCR-mediated amplification of a part of its 16S rRNA gene (16S rDNA). Because there is very little intraspecies variation in these molecules, they are not suitable as targets for epidemiologic investigations. However, the intergenic spacer region between the 16S and 23S rDNAs is usually much more variable and has repeatedly been used for epidemiologic purposes. We have therefore amplified the spacer region of T. whippelii directly from clinical specimens from nine independent Swiss patients with Whipple’s disease by PCR with primers complementary to the 3′ and 5′ ends of the 16S and 23S rDNAs, respectively. The amplicons were directly sequenced and the sequences were compared to the T. whippelii reference sequence in GenBank/EMBL (accession no. X99636). Complete sequence homogeneity was found between the samples from our nine patients; the spacer sequence was also identical to the reference sequence. However, the sequences corresponding to the 3′ and 5′ ends of the 16S and the 23S rDNAs of T. whippelii, respectively, differed from the respective sequences in GenBank/EMBL. The same sequence found in our patients was then found in a sample from the German patient from which the published sequence had been derived. We conclude that the 16S-23S rDNA spacer region seems to be very conserved in T. whippelii and that the respective reference entry in public databases should be revised.